Resistance towards wiki for collaborative learning among undergraduates - Muhammad Abdul Basar, S.M.; Yusop, F.D. (2014)
Wiki is an asynchronous online collaborative tool which can be used to for teaching and learning purposes. This study explored the issues related to undergraduates’ resistance in using Wiki for collaborative learning. Findings revealed that students’ resistance were related to the technical constraints of Wiki, students’ commitment and interest towards the course, initial hands-on exposure to Wiki, and also the importance of peer contributions.